Comparative Study of Non-descent Vaginal Hysterectomy with Total Abdominal Hysterectomy - Shrestha, Rubina; Shrestha, Subha; Ray, Satindar (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Hysterectomy is the most common operation performed by gynecologist worldwide. In the present era emphasis is given on minimal invasive surgery so Non-Descent Vaginal Hysterectomy (NDVH) has gained more interest over Total abdominal Hysterectomy (TAH). NDVH has several benefits over TAH in terms of blood loss, operating time, post-operative complications, recovery and hospital stays. The objective of the study was to compare the clinical outcome of NDVH over TAH with respect to operating time, blood loss, hospital stays, intraoperative and early postoperative complication and to find out the most efficient route for hysterectomy. Methods The study was conducted at College of Medical Science-Teaching Hospital, Bharatpur, Chitwan, Nepal between May 2017- May 2020. Fifty cases each of NDVH and TAH group fulfilling the selection criteria were included in the study. Outcome was measured on the basis of operating time, blood loss, hospital stay and intra an d post-operative complications. Results Baseline characteristics were similar between both the groups. The most common indication for hysterectomy in both the group was fibroid uterus. There was no intra-operative complication in NDVH group but in TAH group bowel injury was encountered in 3 cases. The operating time, blood loss, hospital stay and post-operative complications were less in NDVH as compare to TAH Conclusions NDVH is the better choice of surgery than TAH for the non-prolapsed uterus, size less than 12 weeks with benign pathology.